Contribution of synchrotron radiation to photoactivation studies of biomolecular ions in the gas phase. Issue 6 (17th December 2013) - Giuliani, Alexandre; Milosavljević, Aleksandar R.; Canon, Francis; Nahon, Laurent
Abstract Photon activation of ions in the visible and ultraviolet range attracts a growing interest, partly for its promising applications in tandem mass spectrometry. However, this task is not trivial, as it requires notably high brilliance photon sources. Hence, most of the work in that field has been performed using lasers. Synchrotron radiation is a source continuously tunable over a wide photon energy range and which possesses the necessary characteristics for ion activation. This review focuses on the array of applications of synchrotron radiation in photon activation of ions ranging from near UV to soft X‐rays. © 2013 Wiley Periodicals, Inc. Mass Spec Rev 33: 424–441, 2014.